From Values to Practice: Developing a Religious Moderation Learning Module for Primary Education - Aam Amaliyah; Yuli Amaliyah; Vonny Aklaqul Karimah (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This study examines the development of integrated learning modules incorporating religious moderation values for Madrasah Ibtidaiyah (MI) and Elementary School (SD) levels as an effort to strengthen value-based education from an early age. The research aims to produce learning modules that are valid, practical, and relevant to the pedagogical needs of Islamic basic education. This study employs a Research and Development (R&D) approach using the 4D model, which consists of the stages of define, design, develop, and limited dissemination. Data were collected through needs analysis, expert validation, teacher practicality assessments, student trials, classroom observations, and evaluation of learning mastery. The results indicate that the developed modules demonstrate a high level of validity based on expert judgment and are considered very feasible by teachers as instructional users. Furthermore, the modules were positively received by students and effectively promoted active engagement in the learning process. Evaluation of learning mastery revealed that the majority of students achieved the expected learning outcomes. These findings suggest that religious moderation values can be systematically and contextually integrated into learning modules at the basic education level. This study contributes practically to teachers and Islamic education managers in developing value-based learning and enriches academic discourse on religious moderation and character education through a product development approach.